Leveraging Islamic Fintech to Improve Financial Inclusion - World Bank (World Bank, Kuala Lumpur, 2020)
Islamic finance is a fast-booming segment of global finance. Serving a core population of 1.8 billion Muslims world-wide and a wider global ethical finance audience, its role is growing in global significance especially as it relates to global social financing needs. The global fintech revolution is having a similar impact for Islamic finance through the evolution of a nascent Islamic fintech ecosystem. The purpose of this report is to evaluate the global developments in the area of fintech solutions by Islamic financial institutions (IFIs) and its impact on financial inclusion within its core markets. The core audience of this report are financial services institution leadership, and government policymakers, especially across the core markets of Islamic finance.